Influence of Whole Blood on Standard Curve for Heparin Measurement - Possible Heparin Binding by Red Cells - Melissari, E; Thye, C; Scully, M F; Kakkar, V V (Thrombosis and Haemostasis, 1989)
Measurement of heparin ex vivo is usually with reference to standard curve prepared with a “spiked” normal human plasma pool (NHP). When the calibration curve was prepared by addition of heparin to whole blood before plasma separation, although the linear relationship was maintained the slope was increased in comparison to the classical standard calibration curve. It is concluded that the preparation of the calibration curve by addition of heparin to NHP may give erroneously high heparin levels in treated patients’ plasma, leading perhaps to inappropriate dosage. It was also observed that when heparin was added to blood of different haematocrit (prepared by addition of washed RBC to plasma) and plasma prepared, the subsequent APTT was decreased with the fall in haematocrit; suggesting that the laboratory monitoring of heparin treatment should take into account the patient’s haematocrit.
Keywords: Heparin assay; LMW heparin; Haematocrit; Heparin activity